2020
DOI: 10.1001/jamanetworkopen.2020.5842
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Deep Learning Model for Non–Small Cell Lung Cancer Survival

Abstract: IMPORTANCE There is a lack of studies exploring the performance of a deep learning survival neural network in non-small cell lung cancer (NSCLC). OBJECTIVESTo compare the performances of DeepSurv, a deep learning survival neural network with a tumor, node, and metastasis staging system in the prediction of survival and test the reliability of individual treatment recommendations provided by the deep learning survival neural network. DESIGN, SETTING, AND PARTICIPANTS In this population-based cohort study, a dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 46 publications
5
114
0
Order By: Relevance
“…Although prior studies have reported the use of machine learning to predict survival for individual cancer types, 13 , 14 few to our knowledge have systematically deployed consistent approaches on as many disease sites as we have, thereby preventing a robust understanding of the diseases in which clinical and pathological features are capable of predicting patient outcomes and which still require more investigation. In light of this, we performed the analyses on clinicopathological and biomolecular features separately, which allowed us to decipher the value of more accessible features first before determining the added benefit of more complex information.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have reported the use of machine learning to predict survival for individual cancer types, 13 , 14 few to our knowledge have systematically deployed consistent approaches on as many disease sites as we have, thereby preventing a robust understanding of the diseases in which clinical and pathological features are capable of predicting patient outcomes and which still require more investigation. In light of this, we performed the analyses on clinicopathological and biomolecular features separately, which allowed us to decipher the value of more accessible features first before determining the added benefit of more complex information.…”
Section: Discussionmentioning
confidence: 99%
“…Deep-learning strategies have been explored to integrate multi-omic data sources into riskstratification models utilizing combinations of diagnostic imaging (Kann et al, 2020b), EHR data (Beg et al, 2017;Manz et al, 2020), and genomic information (Qiu et al, 2020). Furthermore, there is the potential for deep learning to better risk-stratify (She et al, 2020).…”
Section: T4 Risk Stratification and Prognosismentioning
confidence: 99%
“…A tumour's microenvironment, e.g., acidosis, increased interstitial fluid pressure, hypoxia, tissue density, drug wash-out, or obstructed blood flow, is a key player modulating drug's infiltration and killing potential [123]. Learning mechanistic interaction networks are also employed in therapy outcome prediction [96,124] and survival analysis [125]. Such approaches use machine learning algorithms to extract tumour growth patterns in both therapy-free and when following neoadjuvant chemotherapy regimens.…”
Section: Instantiations Of Learning Mechanistic Interaction Networkmentioning
confidence: 99%